Upaya Perbaikan Label Kemasan dan Perhitungan Harga Pokok Produksi Berbasis Job Order UMKM Kue Basah - Oktavia, Chendrasari; Hariyanto, Krisnadhi; Muhandhis, Isnaini (Lembaga Pengabdian kepada Masyarakat Universitas Langlangbuana, 2023)
The eclairs production that still maintains production quality is the production of Lala Cake. Even though this business is increasing over time, this business cannot develop rapidly due to the owner's limitations in managing the business in the form of determining selling prices and inappropriate packaging labeling. Therefore, the service implementation team carries out activities aimed at providing education and training to partners regarding business management in the form of determining selling prices through calculating the cost of production and assisting in making packaging label designs. The method used in this activity is giving a questionnaire before the activity regarding the material to be delivered, providing cost classification material and continuing with the cost of production using the job order costing method, then regarding the importance of labels on packaging for MSME partners, comprehensive training and assistance to partners. calculation of cost of production, selling price, and placement of packaging aesthetics. At the end of the activity session, carry out an evaluation stage with partners. This can be seen from the partner's ability to calculate the cost of production, selling price and placing labeling on packaging. The results of this service show that the selling price charged to consumers of Rp. 3,500 does not match the calculation of the cost of production, namely Rp. 4,015; selling price Rp. 4,416 and the packaging label attached is in line with the business owner's expectations for expanding the marketing of his wet cakes.